Catalytic wet torrefaction of biomass waste into bio-ethanol, levulinic acid, and high quality solid fuel - Kostyniuk, Andrii; Likozar, Blaž (Elsevier, 2024)
Creating a sustainable society hinges on efficient chemical and fuel production from renewable cellulosic biomass, necessitating the development of innovative transformation routes from cellulose. In this investigation, we unveil a pioneering chemocatalytic method, utilizing an H-ZSM-5 catalyst within a batch reactor under a nitrogen atmosphere, for the simultaneous one-pot generation of levulinic acid (LA) and/or ethanol during wet torrefaction (WT) of wood cellulose pulp residue (WCPR), yielding high-quality solid fuel. WT parameters include a temperature range of 180 to 260 °C, H2O/WCPR = 10, and reaction durations of 15 to 60 min. Optimal conditions for bio-ethanol production are identified at 180 °C and 15 min, achieving an outstanding 89.8 % selectivity with H-ZSM-5 catalyst. Notably, 69.5 % LA formation occurs at 240 °C after 60 min. Hydrochar assessments include higher heating values (HHVs), decarbonization (DC), dehydrogenation (DH), deoxygenation (DO), enhancement factor, carbon enrichment, surface area, pore diameter, weight loss, and yields of solid, carbon, hydrogen, and energy. The highest carbon content of 76.7 % is attained at 260 °C for 60 min, resulting in an HHV of 29.0 MJ/kg, an enhancement factor of 1.44, and carbon enrichment of 1.59, with a sequence of element removal as DO > DH > DC. A proposed reaction pathway elucidates WT of WCPR with the H-ZSM-5 catalyst, emphasizing the direct cellulose conversion into hydroxyacetone and subsequent ethanol generation through C–C cleavage of hydroxyacetone. Through this research approach, both ethanol and LA can be produced efficiently from renewable cellulosic biomass, offering a novel pathway to reduce dependence on fossil resources.
Supplementary data to this article can be found online at https://ars.els-cdn.com/content/image/1-s2.0-S1385894724012646-mmc1.docx
Keywords: biomass waste; cellulose; wet torrefaction; bio-ethanol; levulinic acid; hydrochar